2016
DOI: 10.1051/shsconf/20162801052
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the parameter of satisfaction with services in tourism: content analysis of online customer reviews

Abstract: Abstract.To increase the competitiveness the hotels have to satisfy their guests' requirements, anticipate their wishes and offer new services; this is quite problematic for the hotel business. The paper considers the opportunities of employing online guest reviews to reveal the hotel ratings and attributes, significant for guests. The implementation of this research method is specified by the quality of information obtained via the internet; it is published on a voluntary basis, statements are initiated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…UGC reveals the real-time sentiments of participants (Wang et al , 2019). Kapilevich et al (2016) measured TS with CT based on UGC, confirming the feasibility of using UGC and providing a theoretical basis for analyzing comments.…”
Section: Methodsmentioning
confidence: 59%
“…UGC reveals the real-time sentiments of participants (Wang et al , 2019). Kapilevich et al (2016) measured TS with CT based on UGC, confirming the feasibility of using UGC and providing a theoretical basis for analyzing comments.…”
Section: Methodsmentioning
confidence: 59%
“…Anagnostopoulou et al (2019) demonstrated that hotel location is a very significant feature when considering profitability, which means that managers should be aware that unchangeable attributes have also an effect on business performance. Kapilevich et al (2016) verified that strategical location allows hoteliers to charge a higher price. Additionally, Baltescu (2016) finds that online reviews in the hotel industry mainly focus on location and distance from attractions.…”
Section: Online Review As a Tool For Hotel Businesses Improvementmentioning
confidence: 87%
“…Nilashi & Ibrahim, 2019a;Ahani, Nilashi, Ibrahim, Sanzogni & Weaven, 2019b;Xu, 2019).As pointed out byAhani, Nilashi and Ibrahim (2019a),Ahani et al (2019c),Ban et al (2019),Bi, Liu, Fan and Zhang (2019),Bulchand-Gidumal et al (2011), Çalı and Balaman (2019), De Pelsmacker, van Tilburg and Holthof (2018,Kapilevich, Karvounis and Zagulova (2016),Li et al (2015),Phillips et al (2015),Phillips et al (2017),Raguseo and Vitari (2017),Singh, Torres and Robertson-Ring (2016),Torres, Adler and Behnke (…”
mentioning
confidence: 92%